Synthesis and characterization of BaTiO3 pellets and thin films - Meor Ahmad Faris, Meor Ahmad Tajudin
Barium titanate was synthesized using a solid state approach and an aqueous method. Solid state syntheses were used to prepare barium titanate pellets using a powder metallurgy method. Appropriate amounts of barium carbonate and titanium dioxide powder were mixed together in an agate mortar. Barium titanate pellets were mixed according to 5 different ratios of Ba/Ti which are 1:0.9, 1:0.95, 1:1, 1:1.05, 1:1.1. Pellets were sintered in air at a temperature 1400 °C. Barium titanate thin films were prepared using an aqueous method. Sol-gel of barium titanate was prepared according to the similar ratios as pellets. Thin films of barium titanate sol-gel were deposited using a desktop printer onto a glass substrate and fired at 400 °C. Both pellets and thin films were characterized by X-ray diffraction, scanning electron microscope, Atomic Force Microscope (thin films only), and impedance spectroscopy. This thesis focuses on determination of dielectric properties of barium titanate including the resistance, capacitance, dielectric constant, relaxation frequency, and loss tangent. The highest density for the barium titanate pellets were 5.90 g/cm3 when a Ba:Ti ratio of 1:1 was used. The average thicknesses of the thin films were 2.89 nm as measured using the atomic force microscope and verified using the scanning electron microscope. Characteristic of barium titanate were observed under various temperatures starting from room temperature up to 450 °C (for pellets) and 300 °C (for thin films). The measured dielectric constant of the pellets at 10 kHz (at room temperature) varied from a maximum of 2810 to a minimum of 1375. Samples with Ba:Ti ratio of 1:1 show the highest dielectric properties. The highest dielectric constant was measured at 100 °C for stoichiometric samples. X-ray diffraction result shows the production of a secondary phase, Ba2TiO4 when barium excess of 5 % or 10 % was added. The barium titanate thin films showed lower crystallinity than the pellets. X-ray diffraction peak broadening measurements of the thin films show an average crystallite size of 14 nm compared to 110 nm for the pellets. Impedance spectroscopy of the barium titanate pellets show the presence of a resistive grain boundary component, a conductive bulk component as well as a ferroelectric third component. The presence of these components were verified via Curie Weiss plots where applicable. The barium titanate thin films did not show the presence of the ferroelectric component. The dielectric constant of the pellets (ɛ= 2810) were significantly higher than the dielectric constant of the thin films (ɛ = 342) and this was attributed to the lower crystallinity of the thin films.